Thanking Expression Used By The Characters In The Luca Movie (A Pragmatic Analysis) - Richa Yusrin Fanida; Koesoemo Ratih (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This study seeks to explain the type of thank-you expression categories and establish the strategy of thank-you expression employed by the character in the movie Luca. The method used in this study was descriptive qualitative. This study used English utterances with thanking expressions as data. The data was documented. Types of thanking expressions were evaluated using Hymes (1972), and strategies of thanking expression were analyzed using Aijmer (1996). In this research, eight types of thank-you expressions were found. The study indicated that 33% of participants acknowledged a major favor, 17% acknowledged a favor, and 11% dismissed a service, ended the conversation, and used irony, sarcasm, or bluntness. 6% of data reveals thanking someone, making them feel good, and negative requests. Moreover, there are four strategies for saying thank you expressions. The data revealed 67% of the data shows thanking somebody explicitly, 17% stressing one's gratitude, 11% showing appreciation of the act, and 6% showing emotion.